Menyusuri Jejak Kristen di Asia : Sejarah, Perkembangan, dan Dinamika Gereja Menurut Matius 28:19 - Apia Ahlapada; Melda Greace; Malik Bambangan (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2024)
The history of Christianity in Asia encompasses various aspects, including its origins, development, and the dynamics of the Church in a continent rich in cultural diversity and traditions. Christianity first entered Asia in the first century through trade routes and the missions of the apostles, spreading rapidly in regions such as Mesopotamia, Persia, and South India. Despite facing significant challenges, such as interactions with major religions like Hinduism, Buddhism, and Islam, as well as complex social and political influences, the Christian Church continued to develop. During the colonial era, European missions provided a new impetus for the spread of Christianity in Asia, though it was often linked with foreign dominance, triggering resistance from local communities. However, the Christian Church in Asia managed to adapt to local cultures and traditions, creating unique expressions of faith in each country or community. This diversity resulted in a unique dynamic within the Church, where Christianity not only survived but thrived despite ongoing social, political, and cultural challenges. In addition to exploring theological and historical aspects, this article also discusses the contributions of the Christian Church in Asia to education, healthcare, and social justice, which played a significant role in shaping social structures and improving the well-being of society. In the modern era, churches in Asia face new challenges such as globalization, religious pluralism, and social change, yet they continue to play an important role in society, both spiritually and socially. Overall, this article portrays Christianity in Asia as an integral part of the continent's history and development, continually adapting to changing times while making significant contributions to society, all while maintaining the core values of its teachings.